PATHOGENETIC APPROACHES AND WAYS OF PREVENTION OF THROMBOEMBOLIC COMPLICATIONS IN TRAUMA PATIENTS - L. Yu. Ivashchuk (International Journal of Medicine and Medical Research, 2018)
Background. The study of thromboembolic complications prevention in trauma patients, who underwent surgery, is presented in the research. Objective. Patients were examined in the Department of Traumatology of Ternopil Municipal Hospital. The first group, 263 people, (18.6 %) consisted of patients with polytrauma and unfavorable prognosis and significant disease severity. The second group comprised patients with combined trauma, 462 people (32.8 %) – a doubtful prognosis for life. The third group, 685 people (48.6 %) involved patients with isolated trauma and positive treatment outcome. Methods. All patients, besides general clinical examination, underwent evaluation of the number of platelets, clotting time, duration of bleeding and study of coagulation (prothrombin index, prothrombin activity thrombotest, total fibrinogen, fibrinogen A, activated recalcification time). The venous system of lower limbs was examined using distal ascending phlebography, color Doppler and duplex ultrasonography SIMENS ACUSSON X 300. Results. A comprehensive prophylaxis of thromboembolic complications was carried out using low-molecular weight heparin as well as essential complex kinetic treatment. Bemiparin in an appropriate dose was administered once a day for 10-14 days of postoperative stay in the hospital. For the patients with moderate risk and high surgery risk (major surgery, over 40 years old in age, obesity, and serious comorbidities) Bemiparin was administered at a dose of 5000-7500 IU per day during patients’ stay in the hospital. In individuals with sub-acute and chronic thrombophlebitis of subcutaneous veins the surgical prophylaxis of thromboembolic complications was performed. Conclusions. The combination of physical, drug and surgical prophylaxis prevented the thromboembolic complications in trauma patients.